On the enhancement of heat transfer fluid for concentrating solar power using Cu and Ni nanofluids: An experimental and molecular dynamics study. (September 2016) - Navas, Javier; Sánchez-Coronilla, Antonio; Martín, Elisa I.; Teruel, Miriam; Gallardo, Juan Jesús; Aguilar, Teresa; Gómez-Villarejo, Roberto; Alcántara, Rodrigo; Fernández-Lorenzo, Concha; Piñero, Jose Carlos; Martín-Calleja, Joaquín
Abstract: This study presents the preparation of nanofluids based on a heat transfer fluid commonly used in concentrating solar power (CSP) plants. They are comprised of a eutectic mixture of diphenyl oxide and biphenyl with Cu and Ni nanoparticles. The nanofluids based on Cu nanoparticles were shown to dramatically improve thermal properties, the heat transfer coefficient being up to 11% higher for the Cu nanofluid compared with the base fluid. Thus, their use in CSP plants could lead to enhancements in their overall efficiency. Accordingly, nanofluids were prepared with varying nanoparticle concentrations and their properties were characterised, including their radiation absorption capacity, viscosity, isobaric specific heat and thermal conductivity. In addition, a molecular dynamics analysis was performed of the experimental systems prepared from a theoretical perspective. This analysis revealed the same tendencies as those found experimentally. That is, adding Cu nanoparticles to the base fluid led to an increase in both the isobaric specific heat and thermal conductivity. In turn, the results of both the experimental and theoretical study showed that nanofluids based on Ni nanoparticles did not have the same effect, the values for isobaric specific heat showing little variation and there was a decrease in thermal conductivity. The theoretical analysis revealed that both of these behaviours can be related to the different internal structures of the nanofluids, which depend on the metal added. These structures are generated by the different interactions between the metal and the molecules of the base fluid. This study improves the understanding of heat transfer mechanisms in this kind of fluids. Graphical abstract: Highlights: Cu-nanofluids show enhanced thermal properties. The heat transfer coefficient is improved for Cu-nanofluids. Molecular dynamics calculations show the metal-fluid interactions. The Cu-fluid interaction is the responsible of the enhanced thermal properties. Thermal conductivity and isobaric specific heat is increased for Cu-nanofluids.